{3×-5y=2(x-y)+1
{3y-3(X-3y)+x=-2-3Y
Soluções para a tarefa
Respondido por
5
3x-5y=2(x-y)+1 (i)
3y-3(x-3y)+x=-2-3y (ii)
(i)
3x - 5y = 2x - 2y + 1
x -3y = 1
(ii)
3y - 3x + 9y + x = -2 - 3y
-2x + 9y = -2
(i) +(ii)
x - 3y = 1 <=> multiplica por 2
-2x + 9y = -2
2x - 6y = 2
-2x + 9y = -2
3y = 0
y = 0 e x = 1
3y-3(x-3y)+x=-2-3y (ii)
(i)
3x - 5y = 2x - 2y + 1
x -3y = 1
(ii)
3y - 3x + 9y + x = -2 - 3y
-2x + 9y = -2
(i) +(ii)
x - 3y = 1 <=> multiplica por 2
-2x + 9y = -2
2x - 6y = 2
-2x + 9y = -2
3y = 0
y = 0 e x = 1
Perguntas interessantes
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás